Increase in the prevalence of Panton-Valentine leukocidin and clonal shift in community-onset methicillin-resistant Staphylococcus aureus causing skin and soft-tissue infections in the Rhine-Neckar Region, Germany, 2012-2016 - Klein, Sabrina; Menz, Monja-Dorina; Zanger, Philipp; Heeg, Klaus; Nurjadi, Dennis (International journal of antimicrobial agents, 2019)
Methicillin-resistant Staphylococcus aureus (MRSA) remains a major challenge for patient care. Community-associated (CA)-MRSA often have a fitness and virulence advantage compared with their nosocomial counterparts. Increased mobility, travel activities and migration accelerate the intercontinental spread of virulent CA-MRSA strains. Outpatient clinics are the most important route of entry for CA-MRSA into hospitals. However, systematic data on CA-MRSA in Germany are limited. In this study, community-onset (CO)-MRSA skin and soft-tissue infection (SSTI) isolates in the Rhine-Neckar Region from 2012-2016 were characterised to gain an insight into their molecular epidemiology and to monitor potential introduction of virulent and dominant MRSA strains into our hospital. A total of 2475 patients with S. aureus SSTI were identified in the outpatient departments of our hospital, of which 94 (3.8%) were MRSA. In addition, 40.4% of the CO-MRSA harboured the virulence factor Panton-Valentine leukocidin (PVL). ST8-t008-MRSA-IVa/c (23.7%; 9/39) and ST80-t044-MRSA-IVc (15.8%; 6/38) were the predominant PVL-positive MRSA. Molecular typing and epidemiological data revealed that 42.6% (40/94) of strains could be traced back to a local origin and 44.7% (42/94) were endemic outside of Europe. Resistance to quinolones, clindamycin and macrolides was common, whilst resistance to trimethoprim/sulfamethoxazole, tetracycline, mupirocin, chlorhexidine and fusidic acid was low. No resistance to rifampicin, fosfomycin or linezolid was observed. This study provides insight into the clonal composition of CO-MRSA in the Rhine-Neckar Region. The increase of PVL-positive MRSA and the introduction of imported strains may affect the local MRSA landscape in the near future and should be monitored closely.
Available online 6 November 2018
Gesehen am 03.04.2019